Perceived efficacy of teachers in Macao and their alacrity to engage with inclusive education. Issue 1 (2nd January 2019) - Monteiro, Elisa; Kuok, Angus C. H.; Correia, Ana M.; Forlin, Chris; Teixeira, Vitor
ABSTRACT: This paper reports findings of a mixed methods study examining private school teachers' perceptions of efficacy in dealing with the challenges presented by inclusive education in Macao. This is highly pertinent after the Government invited consultation to propose changes to amendments of the Decree Law of 1996 concerning the education of students with Special Education Needs (SEN) which will likely see private schools being required to accept these students in the future. Within the context of teacher preparedness for inclusive education, the study found that a number of teachers felt that they were not at all prepared to teach students with SEN. Whilst some teachers suggested that they lacked skills and knowledge in teaching in inclusive classrooms, some felt overwhelmed with the challenges. The teachers proposed that they would need to know how to provide instructional adaptations and modifications to support students with SEN. Implications for continuous development of teacher training and education are discussed within the context of improving teacher efficacy and how private school teachers could better respond to the challenges of inclusive education in Macao.